2006
DOI: 10.1200/jco.2005.04.9551
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Cardiac Tolerability of Trastuzumab in Metastatic Breast Cancer: The M.D. Anderson Cancer Center Experience

Abstract: The risk of cardiac toxicity of long-term trastuzumab-based therapy is acceptable in this population, and this toxicity is reversible in the majority of the patients. In patients who have experienced a CE, additional treatment with trastuzumab can be considered after recovery of cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
199
4
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(223 citation statements)
references
References 32 publications
8
199
4
12
Order By: Relevance
“…Trastuzumab treatment is associated with cardiac dysfunction, with up to 28% of patients experiencing such events (Guarneri et al, 2006), although asymptomatic LVEF declines were more common than symptomatic heart failure (Marty et al, 2003). In this study, three patients experienced LVEF decrease (2.4%); however, with mild severity (Grade 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trastuzumab treatment is associated with cardiac dysfunction, with up to 28% of patients experiencing such events (Guarneri et al, 2006), although asymptomatic LVEF declines were more common than symptomatic heart failure (Marty et al, 2003). In this study, three patients experienced LVEF decrease (2.4%); however, with mild severity (Grade 1).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic and acquired trastuzumab resistance remains a concern (Nahta and Esteva, 2006;Xia et al, 2007). Additional concerns include increased incidence of brain metastasis and risk of both short-and long-term cardiac toxicity associated with trastuzumab therapy (Guarneri et al, 2006;Suter et al, 2007).…”
mentioning
confidence: 99%
“…In a retrospective analysis of older women with early‐stage breast cancer, compared with patients who did not receive either adjuvant chemotherapy or trastuzumab, use of trastuzumab alone or the combination of trastuzumab and anthracycline were associated with absolute increases in the adjusted incidence rate of HF or cardiomyopathy of 14% and 23.8% 51. Similarly, in a retrospective analysis of women treated for metastatic breast cancer at the MD Anderson where 5% had a history of cardiovascular disease (CVD), 26.5% of those who received HER2 targeted therapies had symptomatic HF, which was reversible in the majority of cases 52. Data from the health maintenance organization Cancer Research Network reported the cumulative incidence of HF at 1 and 5 years was 6.2% and 20.1% for women who received a combination of anthracycline and trastuzumab and 3.6% and 12.1% for women who received trastuzumab alone 50.…”
Section: Risk Of Cardiotoxicity Outside Of Clinical Trialsmentioning
confidence: 99%
“…Unlike the anthracyclines, there is no evidence that cumulative doses can predict for cardiomyopathy with trastuzumab. Guidelines advise that patients suffering heart failure due to anticancer agents are managed similarly to those with heart failure due to other causes [13]. However, it is unclear whether cancer patients respond similarly to non-cancer patients.…”
Section: Hepatotoxicitymentioning
confidence: 99%